IMPROVING STUDENTS VOCABULARY ACHIEVEMENT USING VOCABULARY CHARTS TECHNIQUE - winarsih, winarsih (Universitas Islam Balitar, 2019)
This article investigates the technique of teaching vocabulary using Beare’s vocabulary charts. The technique helps to improve students’ mastery of English language and widens their passive and active vocabulary based on related word group areas. The relevancy between vocabularies in the charts is the vocabulary used in students’ daily activities. Adopting a Classroom Action Research, this study collected the data by using vocabulary charts, tests, field notes, checklist, and questionnaires. The result showed that the implementation of vocabulary chart has improved semester three students’ vocabulary achievement at Universitas Islam Balitar, Blitar. 77% of the students passed the minimum criteria of success in the first cycle, and 75% of the students passed the minimum criteria in the second cycle. This technique is beneficial to facilitate students in learning English vocabulary. Vocabulary word charts in teaching English vocabulary are thus recommended.